Assessing Destination Brand Image Chinatown In Term of Semarang City Branding Implementation - Ristianti, Novia Sari; Dewi, Santy Paulla (Jurnal Teknik Sipil dan Perencanaan, 2018)
Abstract. Concerning to city branding, the role of brand image is very important for visitors to remember the tourism destination. The destination brand image can identify by 5 elements of city image, namely path, edge, node, district, and landmark. Semarang Chinatown is one of the historical tourism sites in Semarang that can represent the Semarang's city branding as a "variety of culture" with various cultures and interactions. The aim of this research is to identify the Semarang's City Branding (variety of culture) through destination brand image that revealed by 5 elements of city image. Research methods are carried out in two stages. The first step analysis was described the image of Chinatown area using the descriptive qualitative method. The second step was tried to find the correlation between image of the Chinatown area and the Semarang city branding. Descriptive comparative technique used to compare between the existing and the trend of Chinatown development with theory image of the city. The result of this reserach is identification destination brand image based on 5 elements of the city image. The first element is path with character toponym of alley based on its history as well as the special function as trading area, namely the Gang Baru as traditional market path and Gang Warung as semicircular market path. The second element is edge that shown by the form of Kali Semarang and Gang Beteng which has a history of Chinatown development as centre trade zone in Semarang at the past until now. The third element is node that can be seen from every pagoda located at Chinatown junction (skewers location) because of the fengshui that is embraced by Chinatown communities and it is believed that the location of pagoda can protect against evil and crime. The fourth and fifth elements are districts and landmarks that represented by the Semawis Market and pagoda as the Confucian temple. As a conclusion, Semarang Chinatown's destination brand image as a historical and cultural tourism area of China is memorable and has a strong character.